HUBUNGAN ANTARA PERILAKU CARING PERAWAT DENGAN TINGKAT KECEMASAN PASIEN PRE OPERASI DI RST WIJAYAKUSUMA PURWOKERTO - Junianto, Eko Wahyu; Sekar Siwi, Adiratna; Sumarni, Tri (NHM PRESS, 2025)
Surgery or surgery involves invasive procedures that expose the body part to be treated. The perception of surgical procedures as a life-threatening process causes a person to experience anxiety and the caring behavior of nurses to preoperative patients aims to reduce patient anxiety and be ready to undergo surgery. The purpose of this study was to determine the relationship of nurses' caring behavior with the anxiety level of preoperative patients at RST Wijayakusuma Purwokerto. This type of research is quantitative correlation with a cross sectional approach. The sampling technique was consecutive sampling with a total sample of 30 patients. Data collection was carried out in December 2024. The instruments used were the Amsterdam Preoperative anxiety and Information Scale (APAIS) questionnaire and the CBI-24. The results of the study based on the spearman-rank test obtained a p-value = 0.038 < α (α = 0.05), and a correlation coefficient value of -0.381 which indicates that there is an unidirectional relationship between the level of anxiety and the caring behavior of nurses towards preoperative patients in the Antasena Room RST Wijayakusuma Purwokerto means that when the caring behavior of nurses is high, anxiety in preoperative patients will be low and vice versa.